2004
DOI: 10.1074/jbc.m308975200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nuclear Factor-κB in the Antiviral Action of Interferon and Interferon-regulated Gene Expression

Abstract: Interferons (IFNs)1 are a family of multifunctional cytokines that block viral infection, inhibit cell proliferation, and modulate cell differentiation. Whereas type I IFNs (IFN-␣, IFN-␤, and IFN-) bind to a common cell-surface receptor, the receptor for type II IFN (IFN-␥) is a distinct entity (1). IFNs transduce signals from the cell surface, resulting in selective gene induction through the activation of JAK tyrosine kinases and STAT transcription factors (1-3). Upon JAK-mediated tyrosine phosphorylation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 27 publications
6
58
0
Order By: Relevance
“…For example, tumor necrosis factor-mediated JNK signaling is enhanced in NFB-KO mice (23,24). Moreover, we previously showed that the IFN-induced expression of some ISGs (Mx1 and Nmi) is negatively regulated by NFB, while the expression of other ISGs, such as Ifit1 and Isg15, is enhanced by NFB (6). In the present study, we show that NFB has opposing effects on different ISGs that map to a single genetic locus.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…For example, tumor necrosis factor-mediated JNK signaling is enhanced in NFB-KO mice (23,24). Moreover, we previously showed that the IFN-induced expression of some ISGs (Mx1 and Nmi) is negatively regulated by NFB, while the expression of other ISGs, such as Ifit1 and Isg15, is enhanced by NFB (6). In the present study, we show that NFB has opposing effects on different ISGs that map to a single genetic locus.…”
Section: Discussionsupporting
confidence: 61%
“…1) were induced by IFN␤ in a dose-dependent manner to higher expression levels in NFB-KO cells than in WT cells. Similarly, we showed previously that Mx1 and Nmi were also induced more in NFB-KO cells than in WT cells by IFN in a dose-dependent manner (6).…”
Section: Identification Of Isgs Thatmentioning
confidence: 73%
See 3 more Smart Citations